Smooth Blasting with the Electronic Delay Detonator - Masaaki Yamamoto; Toshiyuki Ichijo; Yoshiharu Tanaka (International Society of Explosives Engineers, 1995)
We utilized electronic detonators (EDs) to investigate the effect of high detonator delay accuracy on overbreak, remaining rock damage, and surface smoothness, in comparison with that of long-period delay detonators (0.25 sec interval) PDs. The experiments were conducted in a deep mine, in a test site region composed of very hard granodiorite with a seismic wave velocity of about 6.0 km/see and a uniaxial compressive strength, uniaxial tensile strength, and Young's modulus of 300 MPa, 12 MPa, and 73 GPa, respectively. The blasting design was for a test tunnel excavation 8 m in cross section, with an advance per round of 2.5 m. Five rounds were performed, each with a large-hole cut and perimeter holes in a 0.4-m spacing charged with 20-mm-diameter water gel explosive to obtain low charge concentration. EDs were used in the holes on the perimeter of the right half, and PDs were used in all other holes.